Exploring Sequences through Variations on Fibonacci - Swain, Gordon A (Ohio Journal of School Mathematics, 2017)
Leonardo Pisano’s word problem, which led to the ubiquitous Fibonacci sequence, provides a point of departure for several explorations. The variations are motivated by more realistic assumptions to the original rabbit problem. Through these activities, students practice data generation, pattern-finding, developing formal proofs, carrying out generalizations, and data analysis. And they might even have some fun!